Traditional Uses of Medicinal Plants of Tharu Ethnic-community of Banke District, Mid-Western Nepal - Yadav, Gyan Bahadur; Chaudhary, Vijay Kumar (Journal of Plant Resources, 2022)
The present study had been conducted in the Tharu community of Rapti-Sonari and Duduwa Rural Municipalities of Banke district, which is rich in tradition, culture and ethnobotanical knowledge. The main aim of this study was to document the native medicinal plants and their uses in the treatment of human ailments/problems among the Tharu community of Banke, District. This study was carried out in March, 2021. The ethnomedicinal data were collected using structured and semi-structured questionnaire interview with 20 key informants, older peoples, local healers, and Guruwas. Altogether 28 traditionally used medicinal plants species were recorded belonging to 27 genera and 21 families, among them Fabaceae was the most dominant family. The most frequently used plants parts were leaves and juice which is the most widely preferred mode of remedy. Older peoples, Guruwa and the traditional healers have high knowledge on the medicinal plants and their uses as compared to younger. Different parts of the same plant species were used for the treatment of more than one ailment using a different mode of remedies; it means single plant species was used in the treatment of multiple ailments. Further study should also be carried out on the documented plant species from study area to utilize them in drug development.